Dealing with losers : the political economy of policy transitions - Trebilcock, M. J. (New York : Oxford University Press, 2014)
Whenever governments change policies there will typically be losers. These losers will have made investments of one kind or another predicated on, or even deliberately by, the pre-reform set of policies. Very few policy changes make everybody better off, but rather re-allocate social benefits and costs in different ways. The issue of whether and when to mitigate the costs associated with policy changes is ubiquitous across the policy landscape. This book explores both normative and positive rationales for transition cost mitigation strategies.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 28, 2014).
Keywords: Policy sciences -- Economic aspects; Political planning -- Economic aspects; Transaction costs; Social policy; Economic policy